Peat stabilization, organic geochemistry and related palynological characteristics of a tropical lowland peat basin in the Kota Samarahan-Asajaya area, west Sarawak, Malaysia / Mohamad Tarmizi Bin Mohamad Zulkifley - Mohamad Tarmizi, Mohamad Zulkifley (2014)

(untitled)
Tropical lowland peat basin was characterized prior to stabilization tests which used the cement-filler-air curing technique. Topogenic, clayey, high-ash, shallow peats (with more naturally occurring in-situ mineral soil filler content) at the basin periphery have higher stabilized strength compared to the deeper, intermediate topogenic to ombrogenic, low-ash peats at the mid-section area (near location KS.TP.08). Nearly all the stabilized cement-filler-peat mix specimens with added mineral soil (silt, clay and fine sands) fillers tested, exhibited brittle or shear failures with no barrelling failure. Stabilized peat specimens from topogenic, marginal, transitional mangrove to shallow peat areas (location KS.TP.0 and KS.TP.02) also exhibited dominantly shear/brittle failures, relatively better, uniform and consistant cylindrical shape, with less deformation, are denser and harder, has lesser cracks, less holes, less indentations or lesser joints/discontinuities at the tamped layer planes. Cement-peat stabilization strength may probably depend highly on the amount of natural/insitu or added mineral soil filler contained within the peat. Strength enhancement by improved densification of the stabilized peat-cement-mineral soil filler mix can be achieved by supplying increasingly more solid particles in the form of mineral soil fillers content. This study indicates that stabilized strength is at the maximum near the dome/basin margin/periphery, decreases at mid-section and increases back again towards basin centre. Stabilized peat strength may be related to basinal lateral vegetation succession. Field identification and von Post classification of the tropical lowland peat shows that there is a lateral variation of peat humification levels and range, corresponding to fibric, fibric to hemic, sapric and hemic to sapric peats, occurring progressively, from margin towards the near-centre of the tropical lowland peat dome or basin. Variations of dominant peat maceral types observed in this study are probably associated with different levels of diagenesis in the humification or peatification process of the tropical iv lowland peats. Source Rock Analyses (compatible Rock-Eval) results show that there is a lateral variation of organic matter types occurring within the top 0 to 0.5 metres peat layer. The hopanes are the dominant pentacyclic triterpanes in the peat alkane fractions sampled from basin periphery to mid section and further towards the near centre of a tropical lowland peat basin (at 0 to 0.5 m depth). The biomarker hopane compounds have 13 to 39 carbons and all show odd over even predominance indicating the true terrestrial depositional environment of the peats. The ββ hopanes biomarkers that indicate immaturity and are commonly present in the peats includes ββ C30 hopane (17 β, 21β (H)-Hopane) and ββ C31 hopane (17β, 21β (H)-Homohopane. The other common hopanes present are C29 hopane (Norhopane), 22Sαβ C31 hopane (17α, 21β (H)-Homohopane) and 22Rαβ C31 hopane (17α, 21β (H)-Homohopane). Logging observations indicate a vertical, downwards, general decrease of peat humification levels with depth. Based on pollen analyses and field observations, the studied peat profiles can be interpreted as part of a progradational deltaic succession. Continued regression of sea levels, gave rise to the development of peat in a transitional mangrove to floodplain/floodbasin environment, followed by a shallow, topogenic peat depositional environment with riparian influence at approximately 2420 ± 30 years (B.P.). Pollen analyses indicates that estuarine and deltaic, brackish to saline water influence may have gradually ceased at approximately 0.5 metres below the lithological boundary between peat and underlying soil (floodplain deposit) in the tropical lowland peat basin.